Research on Green Financial Services and Rural Revitalization under the "Dual Carbon" Goal: Take Xuancheng City as an Example - Wang, Zhiqi; Zhang, Zhuo; Qian, Jinyu; Yang, Jiaming; Li, Deyu (International Journal of Global Economics and Management, 2023)
The path of green financial services for rural revitalization is a booster to achieve the goal of "green development, circular development, and low-carbon development". Although it has broad prospects and initial results, this path is not yet sound and there are still many constraints and bottlenecks. Based on the existing literature and data and the collection of relevant data, this project will provide a positive impact on Anhui from three aspects: supporting green financial services, constraints and solutions Xuancheng City conducts field research. Learn from the local government and residents about the details and deficiencies of the implementation of green financial services and rural revitalization, collect the data we need through questionnaire surveys, establish a model analysis of the data, and give policy suggestions based on the local development situation, so as to actively promote the local area innovation in green finance. It will also optimize the rural revitalization system of green financial services, improve the feasibility of its implementation, promote the use of green financial technology products according to local conditions, and promote the development of rural revitalization in the direction of green and sustainable development across the country.